2023
DOI: 10.3390/pharmaceutics15030872
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of 3D-Printed Titanium Scaffolds with Elastin-like Recombinamers to Improve Cell Colonization and Osteoinduction

Abstract: The 3D printing of titanium (Ti) offers countless possibilities for the development of personalized implants with suitable mechanical properties for different medical applications. However, the poor bioactivity of Ti is still a challenge that needs to be addressed to promote scaffold osseointegration. The aim of the present study was to functionalize Ti scaffolds with genetically modified elastin-like recombinamers (ELRs), synthetic polymeric proteins containing the elastin epitopes responsible for their mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…A 3D-printed titanium mesh should have adequate compressive capacity to avoid any probable collapse or displacement during bone defect restoration, ultimately providing appropriate space and mechanical support for new bone growth [30]. Additionally, the favorable metabolism of bone marrow mesenchymal stem cells, growth factors, and other substances that promote osteogenesis require su cient blood supply, leading to extensive use of 3D-printed implants made from titanium and its alloys due to their ability to provide such adequate blood supply [31].…”
Section: Discussionmentioning
confidence: 99%
“…A 3D-printed titanium mesh should have adequate compressive capacity to avoid any probable collapse or displacement during bone defect restoration, ultimately providing appropriate space and mechanical support for new bone growth [30]. Additionally, the favorable metabolism of bone marrow mesenchymal stem cells, growth factors, and other substances that promote osteogenesis require su cient blood supply, leading to extensive use of 3D-printed implants made from titanium and its alloys due to their ability to provide such adequate blood supply [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have attempted to improve biocompatibility by surface modifying the 3D printed Ti implants. Some of the surface modifications on Ti scaffolds include the application of a homogeneous layer of microporous TiO 2 and calcium-phosphate [96], genetically modified elastin-like recombinamers (ELRs) containing specific cell adhesive (RGD) and osteoinductive (SNA15) moieties [97], coating of aspirin (ASP)/PLGA [98], titania nanotubes via electrochemical anodization and bioactivation through HA coating [99], and chimeric peptides [100]. Studies on adding antimicrobial properties were carried out by surface coating of the Ti implants with gallium nitrate [101], vancomycin hydrochloride [102], flavonoid quercitrin [103], chitosan (CS)-modified MoS 2 coating loaded with AgNPs [104], and calcium titanate [105], to prevent bacterial adhesion and proliferation on the surface.…”
Section: D Printingmentioning
confidence: 99%
“…Liu et al [126] prepared VEGF/BMP-2 core-shell microspheres using coaxial electrostatic spraying technology and loaded the VEGF/BMP-2 core-shell microspheres onto 3D-printed Ti alloy support scaffolds coated with gelatin polymer, thus achieving the sequential release of VEGF and BMP-2 in a composite scaffold system that can effectively promote bone regeneration, providing experimental support and strategies for bone defect repair. Additionally, Guillem et al [127] functionalized the surface of 3D-printed Ti scaffolds with transgenic elastin-like recombinases (ELRs), and the results showed that the improved surface can enhance bone-bonding ability and regulate cell responses.…”
Section: Biologically Active Organic Coatingsmentioning
confidence: 99%